Board age and corporate financial fraud: An interactionist view. Issue 6 (December 2018) - Xu, Yuehua; Zhang, Lin; Chen, Honghui
Abstract: Unlike past studies which have focused on either executives or boards of directors, this study takes an interactionist view to investigate the determinants of corporate financial fraud. We propose that CEOs evaluate the opportunities for financial fraud according to both situational stimuli and their own personal characteristics. As older directors are often more experienced and have more to lose if they fail in their monitoring duties, we expect them to be more capable and to have stronger motivation for monitoring CEOs closely. As such, we propose that a CEO is less likely to engage in corporate financial fraud when the average age of the board of directors increases (i.e., board age). However, when the CEO is older than the board, the CEO may attach less importance to board age when deciding whether to commit fraud. Therefore, we further propose that the CEO–board directional age difference can weaken the effect of board age. Our empirical analyses provide strong support for these hypotheses. Our study contributes to the literature on corporate governance by highlighting the often neglected roles of board age and CEO–board directional age difference in deterring corporate financial fraud.